If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -8 = 2x + -18 Reorder the terms: -8 + x = 2x + -18 Reorder the terms: -8 + x = -18 + 2x Solving -8 + x = -18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + x + -2x = -18 + 2x + -2x Combine like terms: x + -2x = -1x -8 + -1x = -18 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + -1x = -18 + 0 -8 + -1x = -18 Add '8' to each side of the equation. -8 + 8 + -1x = -18 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = -18 + 8 -1x = -18 + 8 Combine like terms: -18 + 8 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| 12+8-5n=42 | | -3b+10=-35 | | D-1/2=10 | | X-(X-5)=16 | | (d+2)(d-5)=-6 | | cosh(x)=1.25 | | 1524x-12+22x=5541+1124x-41 | | 4x-2=9+5(x-3) | | 3q+17+14=19 | | 29=7+x+2+x | | 2x+1+3x+5+6x-31=180 | | (3xy+2yx)3= | | 12-3x=66x | | x/80=35/100 | | X+(X-5)=16 | | 5y-4=3y-18 | | 70=x+4 | | 3x^4-16x^2-81=0 | | g(x)=3f(x+1)-1 | | 28=4n+4-8 | | 4(5x-1)-(x+5)=24 | | 7x+145.5=6 | | f(x)=16x^4+8x^2+1 | | tan(19pi/12 | | 0=-2t(8t-75) | | -28=4n+4-8 | | 11x+1=5x+61 | | f(-4)=x^2-3x+9 | | 29=7+x+2 | | 2l+28=58 | | 5(n-4)=25 | | 6y=5(y+9) |